Bioactivation and reactivity research advances – 2021 year in review. (3rd July 2022) - Jackson, Klarissa D.; Argikar, Upendra A.; Cho, Sungjoon; Crouch, Rachel D.; Driscoll, James P.; Heck, Carley J. S.; King, Lloyd; Maw, Hlaing (Holly); Miller, Grover P.; Seneviratne, Herana Kamal; Wang, Shuai; Wei, Cong; et al.
Abstract: This year's review on bioactivation and reactivity began as a part of the annual review on biotransformation and bioactivation led by Cyrus Khojasteh (see references). Increased contributions from experts in the field led to the development of a stand alone edition for the first time this year focused specifically on bioactivation and reactivity. Our objective for this review is to highlight and share articles which we deem influential and significant regarding the development of covalent inhibitors, mechanisms of reactive metabolite formation, enzyme inactivation, and drug safety. Based on the selected articles, we created two sections: (1) reactivity and enzyme inactivation, and (2) bioactivation mechanisms and safety (Table 1 ). Several biotransformation experts have contributed to this effort from academic and industry settings.